Youths with asthma and their experiences of self-management education: a qualitative systematic review protocol - Mc Cann, Edward; Prizeman, Geraldine; Eustace-Cook, Jessica (My University, 2019)
Asthma is a chronic respiratory condition characterized by episodes of physiological airway narrowing resulting in symptoms of wheeze, breathlessness and mucus production. The trajectory of symptoms varies from mild, moderate to severe episodes that can be fatal. The effects of this chronic disease are known to impact on patients both physically, in restriction of activities, and psychosocially, in terms of quality of life. According to the World Health Organization (WHO), 235 million people suffer from asthma, with 383,000 deaths occurring in 2015. Moreover, youths with a diagnosis of asthma represent the highest percentage (10-11%) across all age groups. Globally, the focus is on minimizing the morbidity and mortality of asthma, recognizing the importance of providing asthma education to promote self-management that may empower people with a diagnosis of asthma. Youths are identified as an at-risk cohort with specific education needs, as this group has a higher risk of life-threatening events. Self-management of a chronic illness such as asthma entails education about the condition, symptom recognition and management, including pharmacological interventions to negate the incidence of asthma exacerbations. However, to effectively engage in self-management of a condition such as asthma, personal commitment and awareness of the consequence of poor adherence is required. Self-management education supports patients with chronic conditions to live their lives to the full. Achieving cognitive maturity entails psychological development, where awareness and understanding of the cause and effect of actions are essential. It is essential for youths to achieve self-management and successful disease associated outcomes. The World Health Organization uses the age parameters of 10 to 24 years to define adolescents, and the United Nations (UN) defines ‘‘youth’’ as those between the ages of 15 and 24 years. This is the age at which cognitive maturity should be attained. The overarching theme emerging from the literature on self-management and youths encompasses issues around developmental maturity, risk taking and the young person’s desire to be perceived as ‘‘normal’’. Internationally, the management of young adults with asthma is a contentious issue. Adolescence and young adulthood is a period of significant transition in cognition and psychosocial development. This transition period occurs for youth on the cusp of ‘‘spectatorship’’ in their disease management, where parents are often concerned about handing over the responsibility of self-management whereas health professionals are encouraging empowerment. Decision-making skills in respect of disease management are tested and influenced through self-regulation and experiences about asthma management plans. A Cochrane review identified a range of decision-making tools for people with asthma, indicating that self-management is linked to improved clinical outcomes and quality of life, educating and empowering patients to become actively involved in their own health management. Studies, although limited in terms of those on adolescents and young adults, have examined barriers to self-management of asthma. These include restriction in participating in sporting activities because of the diagnosis of asthma15and concerns about the effectiveness and long-term effects of medication, particularly in respect of inhaled corticosteroids. Self-management education could help a young person address these barriers. In addition, mental wellbeing and the stresses of living with a chronic disease have been reported as a concern for adolescents and young adults, particularly those who have had life-threatening hospital admissions due to uncontrolled asthma. The perceived barriers to youth self-management of chronic health conditions is also influenced by education. The development of asthma education varies internationally in terms of structure, designated responsibility of educational delivery, and follow-up on their effectiveness. A Cochrane meta-analyses reviewed the effectiveness of asthma educational interventions in children, including adolescents up to 18 years of age, with a diagnosis of asthma, and reported positive benefits, including decreased hospitalizations, returns to the emergency department and improved self-efficacy. However, there is a lack of qualitative evidence specifically identifying youths’ experiences of self-management and asthma education. In addition, criticisms of self-management programs have raised questions about the adoption of adult models of education with chronic illness as being primarily healthcare practitioner driven rather than addressing the expressed needs of adolescents and young people. Successful self-management education interventions, in one longitudinal study of young adults with type 1 diabetes, focused on an individualized holistic approach to disease self-management, demonstrating positive long-term health outcomes for study participants. Moreover, documented asthma diaries of the physical, psychological and social impacts of the disease indicate that an individualized approach supports health professionals in constructing appropriate self-management educational interventions collaboratively with adolescents and young adults. Other studies, including randomized controlled trials and qualitative studies, focus on the role of peers in providing guidance on self-management. These indicate that young people’s input into the development of self-care interventions is important and that peer-led asthma educational interventions lend empathy about asthma experiences and the challenges faced in adapting to living with the condition. Therefore, in this systematic review, we aim to identify, appraise and synthesize available evidence on youths with asthma and their experiences of self-management education. This review will further consider the role of healthcare providers in developing asthma educational interventions informed by the synthesis of evidence from the youth’s viewpoint. This will provide insights which can be utilized by healthcare practitioners in the development of self-management education for this cohort. Consistent with Joanna Briggs Institute methodology, this systematic review will highlight recommendations for practice and policy informed by the quality of the included studies and the contexts in which the studies have been conducted. In order to address the research objectives, we propose conducting a systematic review of evidence generated by qualitative research. A search of the JBI Database of Systematic Reviews and Implementations Reports, the Cochrane Library, CINAHL and PubMed databases did not find any current or planned systematic reviews on this topic.
PUBLISHED
Keywords: Adolescents; Asthma; Educational interactions; Self-management; Youths